The Intermediate Role of Brand Loyalty in the Relationship between Consumer Value and Purchase Intention (Case Study: Consumers of SNOWA Household Appliances in Kermanshah City) - Ghanbari, Mehrdad; Yasemi, Mehdi; Abasi, Ehsan (International Review of Management and Marketing, 2017)
The present study tries to test the mediating role of brand loyalty in relationship between consumer value and purchase intention. The research method is descriptive- correlative and it is specifically of structural equations modeling type which uses Smart PLS software. Statistical population is consumers of SNOWA Appliance Company in Kermanshah city. 384 people were selected as sample regarding confidence interval of 95% and the margin of error 5%. In order to measure research variables a questioner with 5-level Likert type used which its validity confirmed by experts and reliability of used tool obtained by using Cronbach Alpha for functional value 0.876, emotional value 0.799, social value 0.812, brand loyalty 0.892 and purchase intention 0.832 . It shows desirable reliability of research tool. Results showed that functional, emotional, and social values have positive significant impact on consumers, purchase intention of SNOWA household appliance through impact on brand loyalty both directly and indirectly. Keywords: Brand loyalty, consumer value, purchase intention, SNOWA JEL Classification: M1